Stereochemical aspects of nucleophilic addition reactions to alkoxycarbene cations of the iron chiral auxiliary [(eta(5)-C5H5)Fe(CO)(PPh3)] - Davies, S; Fletcher, A; Maberly, T; Thomson, J (2013)
Alkoxy carbene complexes incorporating the iron chiral auxiliary [(η5-C5H5)Fe(CO)(PPh3)] were prepared in good yields from either the corresponding acyl complexes or methoxymethyl complex of the auxiliary. A range of nucleophilic addition reactions to these alkoxy carbene complexes showed moderate to high diastereoselectivities and the reactive conformations of the carbene complexes under these conditions are discussed. © 2013 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.